An OMIC approach to elaborate the antibacterial mechanisms of different alkaloids. (May 2018) - Avci, Fatma Gizem; Sayar, Nihat Alpagu; Sariyar Akbulut, Berna
Abstract: Plant-derived substances have regained interest in the fight against antibiotic resistance owing to their distinct antimicrobial mechanisms and multi-target properties. With the recent advances in instrumentation and analysis techniques, OMIC approaches are extensively used for target identification and elucidation of the mechanism of phytochemicals in drug discovery. In the current study, RNA sequencing based transcriptional profiling together with global differential protein expression analysis was used to comparatively elaborate the activities and the effects of the plant alkaloids boldine, bulbocapnine, and roemerine along with the well-known antimicrobial alkaloid berberine in Bacillus subtilis cells. The transcriptomic findings were validated by qPCR. Images from scanning electron microscope were obtained to visualize the effects on the whole-cells. The results showed that among the three selected alkaloids, only roemerine possessed antibacterial activity. Unlike berberine, which is susceptible to efflux through multidrug resistance pumps, roemerine accumulated in the cells. This in turn resulted in oxidative stress and building up of reactive oxygen species, which eventually deregulated various pathways such as iron uptake. Treatment with boldine or bulbocapnine slightly affected various metabolic pathways but has not changed the growth patterns at all. Graphical abstract: Image 1 Highlights: Antibacterial mechanism of action of three aporphine alkaloids was evaluated. Bulbocapnine and boldine were not active whereas roemerine had significant activity. Accumulation of roemerine resulted in building up of reactive oxygen species. Roemerine has shown potential for the development of a new antibacterial drug lead.